Depression in older people is underdiagnosed. - Allan, C; Valkanova, V; Ebmeier, K (CMP Information Ltd., 2014)
Depression is more common in old age than dementia yet is underdiagnosed and undertreated. It is important to recognise that patients may not always present in a typical way, features that may indicate depression include anxiety, a preoccupation with somatic symptoms, and a change in function. The presence of understandable triggers and causes should not deter GPs from offering treatment, as long as symptoms are pervasive and continuously persist beyond two weeks. Age-related disabilities and changes to physical health are major risk factors for depression in older people. Vascular diseases, including stroke, MI and diabetes increase the risk of depression, both through direct effects on the brain and the psychological effects. Likewise, dementia is a risk factor for depression. Psychological factors such as loneliness and loss of a valued role, as well as social factors related to retirement, bereavement and reduced independence may also increase the risk. Patients with a previous history of depression and anxiety disorders are at increased risk of depression in later life. Assessment and diagnosis are largely based on a careful history. This should focus on eliciting current features of depression, which have been present for at least two weeks, and are associated with a significant change in function. It is important to exclude organic disorders including anaemia, B12 and folate deficiency, and hypothyroidism that may mimic symptoms of depressive disorder. Referral to specialist mental health services is indicated in the following cases: diagnostic difficulty, poor response to treatment, psychotic symptoms, significant psychiatric comorbidity or a risk of self-neglect or suicide.